2017
DOI: 10.1016/j.antiviral.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

APRIL:TACI axis is dispensable for the immune response to rabies vaccination

Abstract: There is significant need to develop a single-dose rabies vaccine to replace the current multi-dose rabies vaccine regimen and eliminate the requirement for rabies immune globulin in post-exposure settings. To accomplish this goal, rabies virus (RABV)-based vaccines must rapidly activate B cells to secrete antibodies which neutralize pathogenic RABV before it enters the CNS. Increased understanding of how B cells effectively respond to RABV-based vaccines may improve efforts to simplify post-exposure prophylax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Furthermore, cytomegalovirus also increases human tonsillar B cell survival by stimu-lating the expression of BAFF and BAFF-R on these cells (137). In contrast to cytomegalovirus, the involvement of the APRIL-TACI axis in host resistance appears to be questionable because while rabies virus induces APRIL expression in murine B cells, immunization with a recombinant rabies vaccine expressing APRIL does not improve antibody responses, and virus-specific plasma cell generation is not diminished in immunized TACI-deficient mice (138).…”
Section: Viral Infections Of the Central Nervous Systemmentioning
confidence: 99%
“…Furthermore, cytomegalovirus also increases human tonsillar B cell survival by stimu-lating the expression of BAFF and BAFF-R on these cells (137). In contrast to cytomegalovirus, the involvement of the APRIL-TACI axis in host resistance appears to be questionable because while rabies virus induces APRIL expression in murine B cells, immunization with a recombinant rabies vaccine expressing APRIL does not improve antibody responses, and virus-specific plasma cell generation is not diminished in immunized TACI-deficient mice (138).…”
Section: Viral Infections Of the Central Nervous Systemmentioning
confidence: 99%
“…In immunization studies for rabies virus, RABV viral vector immunogens expressing membrane-anchored BAFF have been shown to be capable of inducing faster and higher titers of neutralizing antibodies toward RABV antigens without adversely affecting the longevity of the immune response [122]. Conversely, in a separate study, anchoring of APRIL to RABV viral vectors had no effect on antibody responses, and APRIL co-engagement did not improve the generation of LLPCs [123]. These studies are some of the first to assess whether the addition of molecular adjuvants can affect the longevity of the induced memory response through the generation of LLPCs.…”
Section: Tumor Necrosis Family (Tnf) Receptorsmentioning
confidence: 96%
“…We previously showed that expressing secreted BAFF, but not a proliferating inducing ligand (APRIL), from a recombinant RABV-based vaccine targets the extrafollicular pathway of B cell differentiation and improves rabies vaccinations [31, 32]. However, this approach requires viral gene expression in-vivo to produce BAFF, eliminating its potential as an inactivated vaccine.…”
Section: Introductionmentioning
confidence: 99%